Political culture in Bangladesh : perspectives and analysis : selections from the journal of Bangladesh studies - Andaleeb, Dr. Syed Saad (Bangladesh Development Initiative : University Press, 2007)
Contributed articles on various aspects of history of Bangladesh serialized earlier in Journal of Bangladesh studies.